Advances in epitope molecularly imprinted polymers for protein detection: a review. Issue 14 (6th April 2021) - Wang, Xindi; Chen, Gang; Zhang, Pan; Jia, Qiong
Abstract : Epitope molecularly imprinted polymers (EMIPs) are novel imprinted materials using short characteristic peptides as templates rather than entire proteins. Abstract : Epitope molecularly imprinted polymers (EMIPs) are novel imprinted materials using short characteristic peptides as templates rather than entire proteins. To be specific, the amino acid sequence of the template peptide is the same as an exposed N- or C-terminus of a target protein, or its amino acid composition and sequence replicate a similar conformational arrangement as the same amino acid residues on the surface of the target protein. EMIPs have a good application prospect in protein research. Herein, we focus on classification of epitope imprinting techniques, methods of epitope immobilization on matrix materials including boronate affinity immobilization, covalent bonding immobilization, physical adsorption immobilization and metal ion chelation immobilization, and application of EMIPs in peptides, proteins, target imaging and target therapy fields. Finally, the main problems and future development are summarized.